2018
DOI: 10.1038/s41421-018-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Response dynamics of midbrain dopamine neurons and serotonin neurons to heroin, nicotine, cocaine, and MDMA

Abstract: Heroin, nicotine, cocaine, and MDMA are abused by billions of people. They are believed to target midbrain dopamine neurons and/or serotonin neurons, but their effects on the dynamic neuronal activity remain unclear in behaving states. By combining cell-type-specific fiber photometry of Ca2+ signals and intravenous drug infusion, here we show that these four drugs of abuse profoundly modulate the activity of mouse midbrain dopamine neurons and serotonin neurons with distinct potency and kinetics. Heroin strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 70 publications
(92 reference statements)
5
33
3
2
Order By: Relevance
“…For example, some opioids produce dramatic increases in dopamine, whereas others have very little effect (Gottås et al, 2014;Vander Weele et al, 2014). Furthermore, electrophysiological experiments have shown that neurons in the striatum respond in a very different manner to heroin versus cocaine self-administration (Chang et al, 1998;Wei et al, 2018), suggesting that the effects of the two drugs are encoded differently in this brain area.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some opioids produce dramatic increases in dopamine, whereas others have very little effect (Gottås et al, 2014;Vander Weele et al, 2014). Furthermore, electrophysiological experiments have shown that neurons in the striatum respond in a very different manner to heroin versus cocaine self-administration (Chang et al, 1998;Wei et al, 2018), suggesting that the effects of the two drugs are encoded differently in this brain area.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate that FLiCRE can detect elevated neural activity in vivo , we injected AAVs encoding FLiCRE and TRE-mCherry in the ventral tegmental area (VTA) of wildtype mice and implanted an optical fiber above the VTA to deliver blue light. To elevate calcium levels in the VTA, we injected mice with nicotine intraperitoneally (Wei et al, 2018) and delivered blue light to the VTA for 15 min. ~18 hrs later we analyzed the TRE-mCherry expression ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Cocaine blocks dopamine reuptake in synapses, and dopamine accumulated in the synapse increases the activity of inhibitory neurons from the NAc, resulting in reduction of brain activity 53 . On the other hand, heroin suppresses inhibitory neurons projecting to the ventral tegmental area (VTA), resulting in augmentation of VTA activity and dopamine release 54 . Therefore, as cocaine and heroin differently affect the transmission of neurotransmitters including dopamine, it is believed that expression of chemical synaptic transmission‐related genes may also be different between the two drugs.…”
Section: Discussionmentioning
confidence: 99%